Smart variable pitch propeller system for unmanned aerial vehicles - Manchin, Anthony; Mahmod Lafta, Waail; Viet Dao, Dzung (International Journal of Engineering and Technology, 2019)
This paper aims to develop a closed-loop control system for maximum efficiency of variable pitch propeller systems, which utilize mechanical mechanism to change the pitch of the rotor blades in a full size plane, while this system cannot use in a small size plane, specifically, for battery powered unmanned aerial vehicles (UAV’s), the system seeks to maintain the optimal angle of attack of the propeller so as to maintain the maximum efficiency of the propeller throughout all stages of flight. The variable pitch propeller is controlled by a micro-controller and is governed by the relative airspeed of the propeller. When applied to UAV it results in an over-actuated control system. This article proposes an experimental model for a variable pitch propeller, in which thrust and power consumption are optimized. The proposed novel approach is analyzed and discussed, while the efficiency of the variable pitch propellers is being evaluated by extended simulation and experimental results.